2018
DOI: 10.1136/bmjopen-2017-016853
|View full text |Cite
|
Sign up to set email alerts
|

A discrete choice experiment to determine facility-based delivery services desired by women and men in rural Ethiopia

Abstract: ObjectivesDespite global efforts to increase facility-based delivery (FBD), 90% of women in rural Ethiopia deliver at home without a skilled birth attendant. Men have an important role in increasing FBD due to their decision-making power, but this is largely unexplored. This study aimed to determine the FBD care attributes preferred by women and men, and whether poverty or household decision-making are associated with choice to deliver in a facility.Setting and participantsWe conducted a cross-sectional discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 61 publications
1
20
1
Order By: Relevance
“…The study nding shown that, awareness on skilled delivery and number of birth were signi cantly associated with skilled delivery care utilization among the marginalized mothers in the study area. The awareness of mothers about delivery care is comparable with ndings of the previous study, but conversely, number of birth was not similar with previous ndings (12,22). This discrepancy of the ndings might be due to difference in access to health service in different communities.…”
Section: Resultssupporting
confidence: 47%
“…The study nding shown that, awareness on skilled delivery and number of birth were signi cantly associated with skilled delivery care utilization among the marginalized mothers in the study area. The awareness of mothers about delivery care is comparable with ndings of the previous study, but conversely, number of birth was not similar with previous ndings (12,22). This discrepancy of the ndings might be due to difference in access to health service in different communities.…”
Section: Resultssupporting
confidence: 47%
“…Barriers to accessing skilled delivery services in rural Sub-Saharan Africa are well documented and commonly cited factors include: fear of mistreatment or abuse in facilities [14,15], long distance and difficulty in access [9], poverty and education [9], lack of decision-making power and support [8,16], other cultural issues such as birth position and preference for traditional birth attendants [13,17], lack of knowledge of risk and promotion of health seeking behavior [18].…”
Section: Increase Coverage Of Health Facility Delivery From 50mentioning
confidence: 99%
“…The majority of existing literature on DCEs in relation to maternity care in LMICs has focussed on preferences for intrapartum care, generally with the aim of understanding how to encourage more women to birth in healthcare facilities [7][8][9][10][11][12]. Only one prior DCE regarding antenatal care was identified.…”
Section: Introductionmentioning
confidence: 99%